THE EFFECT OF MANAGEMENT EDUCATION TRAINING CENTER (ETC), STRATEGIC BRAND MANAGEMENT, AND MARKETING MANAGEMENT ON PERFORMANCE OF ETC INDRAGIRI HULU REGENCY - Ziko Fransinatra; Yenny Iskandar; Gita Sari Gustika (JURNAL MANAJEMEN DAN BISNIS, 2020)
Education and Training Center (ETC) is an institution which is responsible for increasing the human resources capability to compete in job fields and industry. It also assists government to decrease unemployment. The quality of the ETC determines the output produced and the public's trust to gain knowledge in non-formal educational institutions. In this study, it was found that the influence of the three variables including ETC management, strategic brand management and marketing on ETC performance. Then, the variable that has the greatest contribution to the ETC performance is management and continued with marketing. In ETC management, careful planning should be paid to realizing the development of ETC in the future, and of course always trying to improve and the attitudes of educators and educational staff in ETC so that they become skilled workers who support the realization of the goals of the institution. Furthermore, it is also necessary to take a stance to make improvements to previous program failures in achieving future targets. Furthermore, in Strategic Brand Management, ETC needs to formulate short-term, medium-term and long-term goals so that it needs to strive to build a brand positioning in the community. On the marketing variable, ETC should reconsider the amount of costs offered for the program, and ETC managers should pay attention to the comfort of the community / consumers and increase program promotion to get to the market value. it is also necessary to take a stance to make improvements to previous program failures in achieving future targets. Furthermore, in Strategic Brand Management, ETC needs to formulate short-term, medium-term and long-term goals so that it needs to strive to build a brand positioning in the community. On the marketing variable, ETC should reconsider the amount of costs offered for the program, and ETC managers should pay attention to the comfort of the community / consumers and increase program promotion to get to the market value. it is also necessary to take a stance to make improvements to previous program failures in achieving future targets. Furthermore, in Strategic Brand Management, ETC needs to formulate short-term, medium-term and long-term goals so that it needs to strive to build a brand positioning in the community. On the marketing variable, ETC should reconsider the amount of costs offered for the program, and ETC managers should pay attention to the comfort of the community / consumers and increase program promotion to get to the market value.The purpose of this study is to explain the influence of ETC Management, Strategic Brand Management and marketing on the performance of ETC in Indragiri Hulu Regency.. The results of this study indicate the influence of ETC Management, Strategic Brand Management and marketing on the performance of ETC in Indragiri Hulu Regency.